2017
DOI: 10.3389/fmicb.2017.00348
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic and Differential Activation of σB and PrfA in Listeria monocytogenes at the Single Cell Level under Different Environmental Stress Conditions

Abstract: During host infection, the foodborne pathogen Listeria monocytogenes must sense and respond to rapidly changing environmental conditions. Two transcriptional regulators, the alternative sigma factor B (σB) and the Positive Regulatory Factor A (PrfA), are key contributors to the transcriptomic responses that enable bacterial survival in the host gastrointestinal tract and invasion of host duodenal cells. Increases in temperature and osmolarity induce activity of these proteins; such conditions may be encountere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 77 publications
3
17
0
Order By: Relevance
“…Heterogeneous σ B activity has also been observed in L. monocytogenes in stressed and non‐stressed cells (Utratna et al, ; Utratna et al, ; Guldimann et al, ). This heterogeneity in σ B activity might lead to a specialized sub‐population resulting in ‘bet‐hedging’ strategy that would maximize the survival chances in adverse environments (Eldar and Elowitz, ; Guldimann et al, ). Interestingly, the existence of specialized sub‐population has been recently reported for toxin gene expression in C. difficile .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Heterogeneous σ B activity has also been observed in L. monocytogenes in stressed and non‐stressed cells (Utratna et al, ; Utratna et al, ; Guldimann et al, ). This heterogeneity in σ B activity might lead to a specialized sub‐population resulting in ‘bet‐hedging’ strategy that would maximize the survival chances in adverse environments (Eldar and Elowitz, ; Guldimann et al, ). Interestingly, the existence of specialized sub‐population has been recently reported for toxin gene expression in C. difficile .…”
Section: Discussionmentioning
confidence: 97%
“…Thus, we assumed the iron-sulphur flavoprotein, CD2684, could contribute to σ B activation in C. difficile. Despite several attempts, we were unable to inactivate CD2684 by allele genetic exchange or ClosTron (Heap et al, 2007;Heap et al, 2010) suggesting that CD2684 could be essential in C. difficile. Thus, using the allele exchange strategy, we integrated the entire P tet element from pRPF185 upstream of the translational initiation codon of CD2684 into the chromosome of both the 630Δerm and the sigB mutant strains (Fig.…”
Section: Study Of the Role Of Cd0007 And Cd0008mentioning
confidence: 89%
See 1 more Smart Citation
“…It can form biofilms that are resistant to the external environment in animal foods and on the surface of processing containers [3] . Many studies have found that the strong viability and pathogenicity of LM are closely associated to its environmental stress factors and virulence factors [4,5] . To survive in stress conditions, LM has to modulate its transcriptions of related genes constantly to adapt to the different environments.…”
Section: Introductionmentioning
confidence: 99%
“…To survive in stress conditions, LM has to modulate its transcriptions of related genes constantly to adapt to the different environments. Despite LM possesses many regulatory proteins to modulate gene expression, environmental stress factor Sigma B [4,5] , positive regulatory factor PrfA and response regulator VirR [6,7] appear to play predominant roles in LM survival and infection. In recent years, studies have found that noncoding RNAs (ncRNAs) in LM can form complex regulatory networks with regulatory molecules such as PrfA, Sigma B and VirR, which precisely regulate the virulence and stress response-related genes of LM at transcription, posttranscription, and translational levels [6,8] .…”
Section: Introductionmentioning
confidence: 99%